Increasing the sensitivity of terahertz split ring resonator metamaterials for dielectric sensing by localized substrate etching - Meng, K.; Park, S. J.; Burnett, A. D.; Gill, T.; Wood, C. D.; Rosamond, M.; Li, L. H.; Chen, L.; Bacon, D. R.; Freeman, J. R.; Dean, P.; Ahn, Y. H.; et al. (Optics Express, 2019)
We demonstrate a significant enhancement in the sensitivity of split ring resonator terahertz metamaterial dielectric sensors by the introduction of etched trenches into their inductive-capacitive gap area, both through finite element simulations and in experiments performed using terahertz time-domain spectroscopy. The enhanced sensitivity is demonstrated by observation of an increased frequency shift in response to overlaid dielectric material of thicknesses up to 18 µm deposited on to the sensor surface. We show that sensitivity to the dielectric is enhanced by a factor of up to ∼2.7 times by the incorporation of locally etched trenches with a depth of ∼3.4 µm, for example, and discuss the effect of the etching on the electrical properties of the sensors. Our experimental findings are in good agreement with simulations of the sensors obtained using finite element methods.
Keywords: Dielectric sensing; Dielectric sensors; Enhanced sensitivity; Finite element simulations; Frequency shift; Split ring resonator; Substrate etching; Terahertz time domain spectroscopy